Offshore deep convection initiation and maintenance during the HyMeX IOP 16a heavy precipitation event. (17th February 2016) - Duffourg, F.; Nuissier, O.; Ducrocq, V.; Flamant, C.; Chazette, P.; Delanoë, J.; Doerenbecher, A.; Fourrié, N.; Di Girolamo, P.; Lac, C.; Legain, D.; Martinet, M.; et al.
Abstract : During the first special observation period of the HyMeX program dedicated to heavy precipitation over the western Mediterranean, several Mesoscale Convective Systems (MCSs) formed over the sea and produced heavy precipitation over the coastal regions, as for example during IOP (Intensive Operation Period) 16a. On 26 October 2012, back‐building MCSs formed and renewed over the northwestern Mediterranean Sea while producing heavy rain over the French coastal urbanized regions. This paper analyses the storm evolution along with the ambient flow and the initiation and maintenance mechanisms of the offshore deep convection observed during IOP16a. The suites of water vapour lidars, wind profilers, radiosoundings and boundary‐layer drifting balloons over and along the coast of the northwestern Mediterranean offer a unique framework for validating the convective processes over the sea investigated using kilometre‐scale analyses and simulation. The high‐resolution simulation shows clearly that the convective system is fed during its evolution over the sea by moist and conditionally unstable air carried by a southwesterly to southeasterly low‐level jet. The low‐level wind convergence in this southeasterly to southwesterly flow over the sea is the main triggering mechanism acting to continually initiate and maintain the renewal of convective cells contributing to the back‐building system. The convergence line appears when a secondary pressure low forms in the lee of the Iberian mountains. A sensitivity test turning off the evaporative cooling within the microphysical parametrization shows that the exact location of the main convergence area focusing the heaviest precipitation is determined by small‐scale feedback mechanisms of the convection to the environment.